CALCULATION OF THE RESISTANCE OF A LINEAR-STEPPING PLUG WITH A CUT SPHERICAL DISK - Rashidov Nurbek son of Shermamat,; Temirov Isroil Gulomovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:    The  total  traction  resistance  of  linear-step  plow  with  truncated spherical disc was determined as the sum of the traction resistances of disc blades, housings, soil deepeners and truncated spherical discs.